Initiation of Strategic Collaboration between Local Government and NGO to Strengthen Primary Healthcare Services for At-Risk Communities during COVID-19: Lesson Learned from PUSPA - Dhea Keyle Fortunandha; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: This case report aims to summarize the strategic collaboration between the West Java Provincial Government and CISDI in strengthening primary healthcare services for at-risk communities during the COVID-19 pandemic, with a focus on the PUSPA program. Content: The COVID-19 pandemic exposed the vulnerabilities of national healthcare systems, necessitating a shift from curative hospital treatments to preventive measures. West Java’s Governor, Ridwan Kamil, emphasized this need, leading to the allocation of IDR 80 billion towards the PUSPA program. This initiative, in partnership with CISDI, redirected resources from hospitals to community-based health centers (puskesmas), enhancing their capabilities in testing, tracing, and responding to COVID-19. Despite funding limitations, this strategic alliance exemplified the effectiveness of public-private partnerships in crisis management. The PUSPA program demonstrated that collaboration involving multiple parties can yield optimal intervention results, effectively addressing pandemic challenges and positively impacting public health.